PROMOTIONAL MIX INFLUENCES TO CUSTOMERâS INTENTION TO BUY IN SANGAJI MUSIC STORE - Arifin, Irene
Globalization allow people to explore new things outside their own country, music is one of the example that is accessible for people around the world. However, most of music store that sell music through CD has experienced loss in their sales. Sangaji Music is a music store that also experienced this loss. Among all marketing mix, aside from the location, product, and the price that is relatively the same with another music store, Sangaji music only could differentiate themselves through promotion. Promotional mix is the key to attract customers and also generate better sales. Promotional mix that usually used in the music store are advertising, sales promotion, personal selling, and direct marketing that is hopefully could create customer’s intention to buy and could increase the sales. The purpose of this study is to investigate the current perception toward promotional mix in Sangaji Music and to identify the relationship between promotional mix and intention to buy. The methodology used was quantitative method using questionnaires spread to 101 potential customers in Senayan City Mall, Jakarta. The questionnaires used Likert scale to measure the customer perceptions of Sangaji Music promotion mix and intention to buy. The result found that the current perception of promotional mix in Sangaji Music was quite satisfactory. The advertising has the most positive perception, while the personal selling and sales promotion have less compared to advertising. Direct marketing obtained the least positive perception among others, therefore, only direct marketing alone does not have significant impact to the purchase intention.